Performance evaluation of co-firing various kinds of biomass with low rank coals in a 500 MWe coal-fired power plant. (15th November 2016) - Mun, Tae-Young; Tumsa, Tefera Zelalem; Lee, Uendo; Yang, Won
Abstract: Recently in Korea, the co-firing of biomass in existing pulverized coal power plants has become an important mean to comply with the nation's renewable portfolio standard (RPS). This study investigated boiler efficiency, net plant efficiency, and combustion characteristics from co-firing various biomasses along with two coal blends and the combustion of low rank coals through process simulation based on an existing 500 MWe coal fired power plant using a commercial process simulator (gCCS). Five sources of biomass - wood pellet, empty fruit bunch pellet, palm kernel shell, walnut shell, and torrefied biomass were selected as renewable fuels for co-firing. In addition, hardgrove grindability index tests were conducted for a blend of coal (90%) and each selected biomass (10%) based on thermal share input to investigate the milling power consumption of each blended fuel for a more rigorous simulation. The results show quantitatively that when biomass is co-fired the plant efficiency is decreased due to its lower heating value and more power consumption in mills. The plant efficiency of torrefied biomass co-firing was the highest among all biomass co-firing and combustion of low rank coals due to higher energy density and enhanced grindability of torrefied biomass after torrefaction. Highlights: Process simulation for co-firing of various biomasses was performed. HGI tests for fuel blends were conducted to predict milling power consumptions. Net plant and boiler efficiency were investigated and quantitatively analyzed. Grindability and heating value of the fuels mainly affected to the efficiencies.